2013
DOI: 10.1089/jop.2012.0208
|View full text |Cite
|
Sign up to set email alerts
|

Subconjunctival Triamcinolone Acetonide in the Management of Ocular Inflammatory Disease

Abstract: This article highlights the potential of TA to complement the treatment armamentarium of anterior segment inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 71 publications
0
27
1
Order By: Relevance
“…Dexamethasone has been shown to achieve good ocular penetration following sub‐conjunctival injection, with higher levels of concentration in the aqueous and vitreous than when it is administered as a peribulbar injection or orally . Sub‐conjunctival TA has been shown to be efficacious and safe for anterior uveitis and non‐necrotising, non‐infectious anterior scleritis …”
Section: Steroid Preparations and Methods Of Local Administration To mentioning
confidence: 99%
See 1 more Smart Citation
“…Dexamethasone has been shown to achieve good ocular penetration following sub‐conjunctival injection, with higher levels of concentration in the aqueous and vitreous than when it is administered as a peribulbar injection or orally . Sub‐conjunctival TA has been shown to be efficacious and safe for anterior uveitis and non‐necrotising, non‐infectious anterior scleritis …”
Section: Steroid Preparations and Methods Of Local Administration To mentioning
confidence: 99%
“…Where anterior uveitis has not adequately responded to topical corticosteroids, periocular steroids such as sub‐conjunctival dexamethasone may provide greater therapeutic effect with a short duration of action of 1 to 2 days . Similarly, sub‐conjunctival triamcinolone or betamethasone has also been shown to be safe and effective in severe cases of anterior uveitis …”
Section: Uses Of Locally Administered Steroidsmentioning
confidence: 99%
“…Periocular administration of corticosteroids using the subconjunctival route as a depot can be an attractive alternative as it leads to high local drug levels that are necessary to alleviate postoperative inflammation, especially in the setting of a corneal transplant [17–19]. Several studies have reported better clinical outcomes, such as reduction in neovascularization, preservation of corneal clarity and reduction of inflammation, with subconjunctival depot injections of steroids [17,18,2023]. A single subconjunctival corticosteroid administration results in higher drug concentration than several topical administrations [17,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that all treatment groups had clinically meaningful reductions in central subretinal thickness compared with baseline 15 . However, subconjunctival injections of TA have rarely been reported [14][15][16] .…”
Section: Discussionmentioning
confidence: 99%